Scientific substantiation of the concentration of excipients for the manufacture of eye drops Angiolin - L. I. Kucherenko; I. A. Mazur; R. R. Akopian; O. O. Portna; H. I. Tkachenko (Zaporozhye State Medical University, 2021)
Throughout human history, cataracts have been one of the leading causes of blindness. For this disease, we studied the market of drugs of domestic and foreign production. The object of our study was the subgroup S10X Other ophthalmic drugs. Employees of the Department of Pharmaceutical Chemistry of Zaporizhzhia State Medical University (ZSMU) together with specialists of the NGO "Pharmatron" was synthesized a new compound, which was named Angiolin. A rational dosage form in the form of eye drops was proposed for the new drug. Since the drops continue to be the most common and widely used in practice dosage form. We have previously selected the optimal content of the active substance in eye drops. As is known from the technological parameters, eye drops must be isotonic, ie in their composition should be added excipients. The aim of our work is to select the concentration of excipients for the manufacture of eye drops Angiolin. Materials and methods. During the work at the Department of Pharmaceutical Chemistry of ZSMU, three solutions of eye drops Angiolin with different composition were prepared, and later the theoretical osmolarity was calculated. Results. Accurate theoretical calculation of the osmolarity of solutions containing substances with high molecular weight, complex total extracts, and highly concentrated solutions is impossible. Since the excipient was used methylcellulose, it was better to perform such a calculation experimentally, through the determination of osmolality. On the basis of the conducted researches, for correction of osmolarity, we were chosen - sodium chloride. Sodium chloride was selected at a concentration of 7.0 g/l, which creates an osmolality of the drug equal to 234.3 mosmol/kg. The estimated value at the same concentration of sodium chloride was 239.56 mosmol/l. The value of osmolarity of eye drops was calculated from it makes 302,18 mosmol/l that was confirmed the correctness of the chosen concentration of sodium chloride as a part of eye drops. Conclusions. Based on the above, we selected the concentration of excipients for the manufacture of eye drops Angiolin.